Prophylactic measures in patients at high and medium risk of thrombosis (The Peerian Journal, 2024)
Early detection and prevention of deep vein thrombosis of the lower extremities, as well as the prognosis of associated thromboembolic complications (TEC) remain urgent problems on the way to improving surgical care [2], since among the causes of postoperative mortality pulmonary artery thrombosis is 10-21% and ranks 2-3 after peritonitis and cardiovascular failure